2002
DOI: 10.2337/diacare.25.4.712
|View full text |Cite
|
Sign up to set email alerts
|

Additional Lunchtime Basal Insulin During Insulin Lispro Intensive Therapy in a Randomized, Multicenter, Crossover Study in Adults

Abstract: Equal HbA(1c) levels and increasing frequencies of hypoglycemia in the evening overshadow the slight improvement of the evening glucose profiles during a regimen with 2 x NPH daily insulin. Therefore, generalized use of a second injection of NPH insulin at lunchtime cannot be recommended to all adult patients with type 1 diabetes using intensive insulin lispro therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Stades e cols. introduziram uma segunda dose de NPH no almoço no esquema de tratamento intensivo com insulina lispro nas refeições e NPH à noite ao deitar, e mostraram uma melhora da glicemia pré-jantar; no entanto, não houve diminuição da hemoglobina glicada (20).…”
Section: Discussionunclassified
“…Stades e cols. introduziram uma segunda dose de NPH no almoço no esquema de tratamento intensivo com insulina lispro nas refeições e NPH à noite ao deitar, e mostraram uma melhora da glicemia pré-jantar; no entanto, não houve diminuição da hemoglobina glicada (20).…”
Section: Discussionunclassified
“…It can be argued that the lack of improvement in HbA 1c seen in the present study relates to several points of suboptimal clinical management, rather than reflecting how patients choose to use their insulin in everyday practice. For example, some, but not all studies suggest that two or more injections of intermediate‐acting insulin will improve glycaemic control, 14 yet at the end of the study period only 31% of patients were taking NPH insulin two or more times per day. This probably reflects the reluctance of patients, rather than of their health‐care providers, to consider an increased frequency of injections to five or more per day.…”
Section: Discussionmentioning
confidence: 99%
“…Improved glycaemic control appears to be best achieved with multiple injection regimens where the basal dose is optimised, 20,21 although this can be associated with increased hypoglycaemia. 22 Insulin lispro can be mixed with neutral protamine Hagedorn (NPH) without any pharmacokinetic changes. 23 Several studies have also shown improved post-prandial glucose levels in type 1 17,24,25 and type 2 diabetes 26 including adolescents.…”
Section: Insulin Lispro (Lysb28 Prob29-human Insulin)mentioning
confidence: 99%